Antiseden Minat Wisatawan terhadap Pengalaman Imersif di Taman Safari Bogor - Nuraini, Nafila; Aulia, Naila; Rahayu, Fatik (Li Falah: Journal of Islamic Economics and Business, 2025)
This study examines the influence of immersive tourism experiences on the emotional experience and behavioral intention of tourists at Taman Safari Bogor. Data were collected through an online survey and analyzed using AMOS-based Structural Equation Modeling (SEM). The results showed that experiencescape positively affects emotional experience but has no direct effect on behavioral intention. Emotional experience also did not prove significant in shaping tourists' behavioral intentions. This finding indicates that emotional experience must be mediated by other variables, such as satisfaction or emotional attachment, to encourage repeat visit intention. The practical implication is that destination managers need to build experiences that are physically and socially immersive and create deep emotional bonds.